UPAYA MENINGKATKAN HASIL BELAJAR IPA DENGAN METODE DEMONSTRASI PADA SISWA KELAS VI - GUSRA, SRI MAIMI (Dharmas Education Journal (DE_Journal), 2022)
The research problem is the low learning outcomes of students in science teaching and learning activities in class VI. The purpose of this research is to improve the activities and results of students' practice in the learning method so that in this learning method the activities are not only dominated by the teacher. This research is action research research. This research uses a form of action research from Kemmis and Taggart which is in the form of a winding from one cycle to the next. Each cycle includes planning (concept), action (action), observation (observation), and reflection (reflection). The instruments used are syllabus, lesson plans, worksheets. On the other hand, for testing, formative tests are used in the form of fair questions. Information analysis method uses the percentage of completeness. Initial meeting of cycle I, second meeting of cycle I, initial meeting of cycle II, and second meeting of cycle II) are 55%, 65%, 75%, and 95% respectively. On the other hand, in general, cycle I is 68.5% for meeting I, 73.5% for meeting II, for cycle II is 77.25% for meeting I, 84.5 for meeting II. The application of demonstration procedures has a positive effect, students are interested and interested in demonstration procedures so that they become motivated to practice.